Skrining Malaria Puskesmas Hebeybhulu Yoka Kota Jayapura - Tuturop, Katarina L; Asriati; Pariaribo, Konstantina M; Adimuntja, Natalia; Bouway, Dolfinus Yufu; Yufuai, Agustina; Assa, Inriyanti (UNIVERSITAS CENDERAWASIH, 2024)
Clinical manifestations and laboratory examinations can help diagnose malaria. Several methods, such as molecular-based tests, RDT, and microscopic examination by reading thick and thin blood smears, can be used to diagnose malaria through laboratory tests. RDT is an alternative method for malaria diagnosis that targets Plasmodium antigens. It has been widely used around the world. Public Health students from Cenderawasih University, in collaboration with the Hebeybhulu Yoka Health Center, conducted malaria screening using anamnesis and blood examination methods with RDT. The screening practice started on Tuesday, November 4, 2024, and will continue until November 13, 2024. collecting samples from patients receiving treatment at Puskesmas Hebeybhulu Yoka. Based on the screening results, the biggest risk factor contributing to malaria cases is stagnant water, such as ditches, with 11 positive cases (21.2%). Respondents who tested positive for malaria were 82.7%, with 13.6% testing positive for tertian malaria, 2.5% for tropical malaria, and 1.2% for mixed malaria.